Exploring student disability and professional identity: navigating sociocultural expectations in U.S. undergraduate civil engineering programs. Issue 1 (2nd January 2020) - McCall, Cassandra; Shew, Ashley; Simmons, Denise R.; Paretti, Marie C.; McNair, Lisa D.
ABSTRACT: National agencies throughout Australia and the United States (U.S.) have called for broadened participation in engineering, including participation by individuals with disabilities. However, studies demonstrate that students with disabilities are not effectively supported by university systems and cultures. This lack of support can shape how students form professional identities as they move through school and into careers. To better understand these experiences and create a more inclusive environment in engineering, we conducted a constructivist grounded theory exploration of professional identity formation in students who identify as having a disability as they study civil engineering and experience their first year of work. We conducted semi-structured interviews with 24 undergraduate civil engineering students across the U.S. and analysed them using grounded theory techniques. Navigating sociocultural expectations of disability emerged as one key theme, consisting of three strategy types: (1) neutrally satisfying expectations, (2) challenging expectations, and (3) aligning with expectations. Regardless of strategy, all participants navigated sociocultural expectations related to their studies and their disabilities. This theme highlights the ways sociocultural influences impact students' navigation through their undergraduate civil engineering careers. These findings can be used to examine cultural barriers faced by students with disabilities to enhance their inclusion in engineering.